Academic Senate Minutes 2004-05-06 - Academic Senate:::::::::
Agenda amended and approve. Minutes of 4/1/04 approved. Subject Matter Prep Programs approved. Conflict of Interest Policy approved. Special Guest Vice Mayor of Cotati Lisa Moore. Academic Affairs Strategic Planning document First Reading. APC Statement regarding "A New Path for General Education at Sonoma State" First Reading. Dean Les Adler – Discussion of Summer School Funding. Recommendation to continue electronic voting for Senate elections approved. Reports from Provost and APC. Good of the Order.